Screening for Fabry Disease in Young Strokes in the Australian Stroke Clinical Registry (AuSCR) - Malavera, Alejandra; Cadilhac, Dominique A.; Thijs, Vincent; Lim, Joyce Y.; Grabsch, Brenda; Breen, Sibilah; Jan, Stephen; Anderson, Craig S. (Frontiers in Neurology, 2020)
Introduction: Fabry disease (FD) is an X-linked lysosomal storage disorder characterized by a deficiency or absence of alpha-galactosidase A (α-GAL A) enzyme, where stroke can be a serious complication. The aim of this study is to determine the feasibility of centralized screening for FD, among young stroke adults registered in the national Australian Stroke Clinical Registry (AuSCR). Methods: The study was conducted in young (age 18-55 years) survivors of acute stroke registered in AuSCR at hospitals in Queensland, Tasmania, New South Wales, and Victoria during 2014-2015; and who, at the 3-month outcome assessment, agreed to be re-contacted for future research. Descriptive analyses of case identification from responses and specific enzyme and DNA sequencing analyses were conducted for α-galactosidase A (α-GLA) from dried blood spot (DBS) testing. Results: Of 326 AuSCR-identified patients invited to participate, 58 (18%) provided consent but six were subsequently unable to provide a blood sample and two later withdrew consent to use their data. Among the remaining 50 participants (median age 53 years [48–56 years]; 47% female), 67% had experienced an acute ischemic stroke. All males (n=27) had an initial screen for α-GLA enzyme activity of whom seven with low enzyme levels had normal secondary α-GLA gene analysis. All females (n=23) had genetic analysis, with one shown to have a pathogenic c.352C>T p.(Arg118Cys) missense mutation of the α-GLA gene for FD. Conclusions: These data provide logistical data for embedding a process of automated central stroke registry screening for an additional case-finding tool in FD.